2016
DOI: 10.1111/cts.12395
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Class‐Specific Exposure‐Viral Load Suppression Response of HIV Antiretrovirals Using A Model‐Based Meta‐Analysis

Abstract: We applied model‐based meta‐analysis of viral suppression as a function of drug exposure and in vitro potency for short‐term monotherapy in human immunodeficiency virus type 1 (HIV‐1)‐infected treatment‐naïve patients to set pharmacokinetic targets for development of nonnucleoside reverse transcriptase inhibitors (NNRTIs) and integrase strand transfer inhibitors (InSTIs). We developed class‐specific models relating viral load kinetics from monotherapy studies to potency normalized steady‐state trough plasma co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…At the 25‐mg dose, median steady‐state C 24 was approximately 300 nmol/L . Moreover, based on in vitro data, a pharmacokinetic target of approximately 78 nmol/L has been established for efficacy against wild type HIV‐1 based on more than 6‐fold the concentration required for 50% inhibition of wild type HIV‐1 . Nevertheless, optimal exposure would be that associated with the 100‐mg dose, which was evaluated in the pivotal phase 3 trials and found to have robust efficacy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 25‐mg dose, median steady‐state C 24 was approximately 300 nmol/L . Moreover, based on in vitro data, a pharmacokinetic target of approximately 78 nmol/L has been established for efficacy against wild type HIV‐1 based on more than 6‐fold the concentration required for 50% inhibition of wild type HIV‐1 . Nevertheless, optimal exposure would be that associated with the 100‐mg dose, which was evaluated in the pivotal phase 3 trials and found to have robust efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…23 concentration required for 50% inhibition of wild type HIV-1. 31 Nevertheless, optimal exposure would be that associated with the 100-mg dose, which was evaluated in the pivotal phase 3 trials and found to have robust efficacy. 9 Thus, the effect of adjusting the dose regimen of doravirine on steady-state doravirine pharmacokinetics during concomitant administration of rifabutin was projected by nonparametric superposition analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the lower bound of the 90% confidence interval (CI) of the trough concentration of doravirine exceeded this 107 nM threshold after 5 days of dosing (lower bound of the 90% CI for predosing on day 6, 122 nM). Moreover, a model-based meta-analysis that leveraged monotherapy and long-term efficacy data across major drug classes indicated that for NNRTIs in particular, steadystate trough concentrations at least 6-fold above the in vitro 50% inhibitory concen-tration are associated with full efficacy (18). The model-informed efficacy target of 78 nM was therefore exceeded prior to the 3rd dose of doravirine.…”
Section: Discussionmentioning
confidence: 99%
“…MBMA of relationship between in vitro potency-normalized unbound clinical exposures and associated efficacy of successful drugs and failed investigational agents to define exposure targets for molecule libraries in research programs and inform multidimensional optimization coupled with translational PK and PK/safety modeling, and enhance confidence in projected human effective dose range. Illustrative Applications: References 19,20 Which is the most reliable animal model of disease or in vitro test system to maximize confidence in clinical translation to efficacy (or safety) and for projection of human effective (or safe) exposures?…”
Section: Trial Designsmentioning
confidence: 99%
“…19 One recent application of translational MBMA in drug discovery is in antiretroviral drug research. 20 Xu and colleagues conducted a translational MBMA relating the dynamics of clinical viral load suppression by antiretroviral agents sharing a common mechanism of action to their respective in vitro potency-normalized clinical exposures. The in vitro potency assays were conducted in 100% human serum, allowing direct use of clinical total plasma exposures in the translational analysis.…”
Section: Mbma In Drug Discovery and Translational Researchmentioning
confidence: 99%